Game design workshop : a playcentric approach to creating innovative games - Fullerton, Tracy (CRC Press, 2024)
Game Design Workshop puts you to work prototyping, playtesting, and revising your own games with time-tested methods and tools. These skills will provide the foundation for your career in any facet of the game industry including design, producing, programming, and visual design.